Factors contributing towards the acceptance of motor Takaful product amongst Kelantanese / Maisarah Mat Seman - Mat Seman, Maisarah (Faculty of Business and Management, 2011)
This research conducted focusing on the “Factors contributing towards the acceptance of motor Takaful amongst Kelantanese”. As motor Takaful and conventional insurance are quite similar, motor Takaful company was identify certain factors that can contribute to the acceptance of motor Takaful amongst Kelantanese. This study emphasizes on three factors related which knowledge, promotion and confidence of the product. The purpose of this study is to identify the factors contributing to the acceptance of motor Takaful and to measures how strong the relationship between independent variables (knowledge, promotion and confidence) and the dependent variable (acceptance of motor Takaful). This study has two objectives which is to identify the factors contributing towards the acceptance of the motor Takaful product amongst the Kelantanese at Kota Bharu and to determine the most important factor that contributes towards the acceptance of the motor Takaful product amongst the Kelantanese at Kota Bharu The respondents of this study consist of Kelantanese at Kota Bharu and 100 questionnaires had been distributed among them. The process of analysis and interpreting the data has been presented with tables by using reliability test, frequency and descriptive analysis. From the finding, the respondent show good acceptance of motor Takaful with the most factor contributes is confidence factor. The researcher also has come out with few recommendations that can be taken into consideration. Hence, by several recommendation that has been recommended in the Chapter 5 can improve the performance of motor Takaful.